PENERAPAN TEKNOLOGI PENGOLAHAN TERASI UDANG BAGI USAHA KECIL MENENGAH DI KABUPATEN BANGKA SELATAN - Idiar Idiar; Boy Rollastin; Muhammad Setya Pratama; Erwansyah Erwansyah (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
Tanjung Ketapang Village is a centre for making shrimp paste in the South Bangka Regency. Shrimp paste is one of  the superior regional products with quality to be developed to compete in the global market. The stages of processing shrimp paste are drying, mixing salt and then fermentation, pounding shrimp, drying shrimp paste, pounding shrimp paste dough, and molding shrimp paste. The production stages are still carried out traditionally with manual equipment, which requires more energy and time and is less hygienic. The problems faced by the two partners are the production process which is still traditional and manual from beginning to the end of product processing, and conventional marketing systems. Based on problem,s analysis, data were obtained from the technical specifications of the machines needed by partners, namely mixing machines, grinding machines, and shrimp paste drying ovens. The implementation methods applied are identification of partner problems, machine design, machine manufacture and assembly, function testing, training on how to operate and maintain machines marketing management training, and mentoring for both partners. After the implementation of the partner's production process, namely an increase in the production capacity of shrimp paste for the two partners, it was twice as much as the previous production and online marketing media.